Effects of screen decks' aperture shapes and materials on screening efficiency. (1st August 2019) - Davoodi, A.; Bengtsson, M.; Hulthén, E.; Evertsson, C.M.
Highlights: Different aperture shape and different material properties in screen media have an impact on screening performance. DEM can easily and accurately simulate screening operations in accordance with actual conditions. The number of particle bounces on the steel screen deck is less compared to rubber and polyurethane. One layer of particles is not always efficient. Abstract: Screening is a key unit operation for the large-scale separation of materials. There are certain different machine parameters and variables that affect the process of screening. The Discrete Element Method (DEM) is a suitable method to analyze parameters and variables. The main benefit of using the DEM for simulating the screening process is that, as a contact model, it provides the possibility of tracking each particle in the material flow and all collisions between particles and between particles and boundaries. There are different types of materials used for screening media, such as rubber and polyurethane, which are used in modular systems as a panel, and such as steel, which are used as a wire in the mesh. This paper presents how different materials used in screen decks affect the screening process. The materials' strength and elasticity have been examined in order to study how the aperture will change in different materials and how different shapes of the aperture and material of screening media affect the screening performance by analyzing the effect on material flow.